CXCL5 Promotes the Malignant Phenotype of Pancreatic Cancer and Is Associated With Immune Infiltration. - Wang, Tao; Sheng, Jian; Wang, Xiaoguang; Zhu, Minyuan; Li, Shijun; Shen, Yiyu; Wu, Bin (Clinical Medicine Insights: Oncology, 2024)
Background: The significance of CXCL5 in pancreatic cancer is unclear, although it has been implicated in the malignant process of many different types of cancer. Research on the impact of CXCL5 on immune cell infiltration and the malignant phenotype of pancreatic cancer is needed. This study aimed to examine the connection between CXCL5 expression and immune cell infiltration and the malignant phenotype of pancreatic cancer. Methods: Tissue samples and clinical information were collected from 90 patients with pancreatic cancer. Tumour tissues and adjacent tissues were made into a tissue microarray and stained for immunohistochemistry analysis. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and Western blot analysis were performed to measure the expression level of CXCL5. CXCL5-overexpressing/CXCL5-knockdown cell lines were constructed via transfection for cytological experiments. CCK-8, cell apoptosis, cell cycle, cell invasion, and cell colony formation assays were used to detect the effect of CXCL5 on the malignant phenotype of pancreatic cancer cells. Finally, a mouse model of pancreatic cancer was constructed for in vivo verification. Results: Compared with control cells, pancreatic cancer cells overexpressing CXCL5 exhibited increased proliferation, migration, and invasion but decreased apoptosis. Conversely, knockdown of CXCL5 did not enhance the malignant phenotype of pancreatic cancer cells. Spearman correlation analysis indicated that there was a significant negative correlation between CXCL5 levels and the CD8 IRS. However, there was a significant positive correlation between FOXP3 IRS and CXCL5 levels. Conclusions: CXCL5 is highly expressed in pancreatic cancer and promotes the malignant phenotype of pancreatic cancer cells. CXCL5 is associated with immunosuppressive FOXP3 + T-cell infiltration, which facilitates the formation of an immunosuppressive microenvironment (with low CD8 + T-cell infiltration).